Diffusion of tebuconazole into softwood under ambient conditions and its distribution in freshly treated and aged wood. (November 2016) - Kukowski, Klara; Martinská, Veronika; Krishnamoorthy, Gautham; Kubátová, Alena; Kozliak, Evguenii
Graphical abstract: Highlights: Tebuconazole (TAZ) diffusion in softwood was monitored and modeled. Time dependent diffusivities were estimated by experimental and numerical methods. Solvent mass uptake study spanning 6 months revealed 3 distinct diffusion stages. The majority of TAZ diffused 2–4 mm below the wood surface. The TAZ distribution remained constant 6 months after the treatment. Abstract: Due to the nonhomogeneous nature of wood, diffusion of preservatives is a complex, multifactorial process. A proper understanding of this process is essential for the development of enhanced wood treatment protocols ensuring long-term stability of wood products. In order to assess the effectiveness of commercially used wood preservative treatments, the penetration of a representative radiolabeled fungicide in softwood was measured and then modeled using a double-logarithmic model. The longitudinal and surface penetration of 14 C-labeled tebuconazole (TAZ) dissolved in a naphtha-based solvent was investigated at ambient pressure and temperature. Solvent and TAZ time dependent diffusion coefficients were estimated employing both experimental and computational methods using solvent mass uptake data spanning 6 months and complete TAZ immersion data spanning 3 min. Results obtained by these two methods were matching for short treatment times suggesting that the bulk of the TAZ traveled together with the solvent. No TAZ redistribution was observed in treated wood samples upon laboratory aging for 6 months other than subsurface evaporative losses.